"Picturesque Incisiveness": Explaining the Celebrity of James's Theory of Emotion. Issue 2 (10th March 2014) - Wassmann, Claudia
<x xml:space="preserve">Abstract</x> William James is the name that comes to mind when asked about scientific explanations of emotion in the nineteenth century. However, strictly speaking James's theory of emotion does not explain emotions and never did. Indeed, James contemporaries pointed this out already more than a hundred years ago. Why could "James' theory" nevertheless become a landmark that psychologists, neuroscientists, and historians alike refer to today? The strong focus on James and Anglo‐American sources in historiography has overshadowed all other answers given to the question of emotion at the time of James. For that reason, the article returns to the primary sources and places James's work back into the context of nineteenth century brain research in which it developed.